2000
DOI: 10.1001/archpedi.154.11.1108
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Chlamydia in Adolescents and Young Women

Abstract: To measure the proportion of sexually active females aged 15 to 25 years who received a screening test for Chlamydia trachomatis infection during the previous year. Design: Administrative data were used to identify females in the target age range who were likely to be sexually active. Medical record data were reviewed for a sample to determine whether the administrative algorithm was acceptable. Laboratory claims data and medical record data were used to identify females who had had a screening test for chlamy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 34 publications
(27 reference statements)
1
13
1
Order By: Relevance
“…Screening rates varied from 2% to 42% depending primarily on the type of clinic visit (eg, routine visit, acute illness, pregnancy screening, contraceptive counseling). 17 Although we found that the proportion of female physicians in an office was not a predictor of screening after multivariable adjustment, other studies have reached contrasting conclusions. 14 For example, Torkko reported that female providers were more likely to take a sexual history and test for C. trachomatis.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Screening rates varied from 2% to 42% depending primarily on the type of clinic visit (eg, routine visit, acute illness, pregnancy screening, contraceptive counseling). 17 Although we found that the proportion of female physicians in an office was not a predictor of screening after multivariable adjustment, other studies have reached contrasting conclusions. 14 For example, Torkko reported that female providers were more likely to take a sexual history and test for C. trachomatis.…”
Section: Discussioncontrasting
confidence: 68%
“…10 Similar screening rates have also been found by other investigators, with generally higher rates from provider self-report 14,15 and lower rates from administrative data. 16,17 Based on an algorithm driven by managed Vol. 32 • No.…”
Section: Discussionmentioning
confidence: 99%
“…Patient factors include (1) the stigma associated with STDs; (2) lack of awareness of the high prevalence, asymptomatic nature, and serious complications of chlamydial infection; (3) the presence of parents during the examinations of adolescents, which precludes confidential sexual risk assessment; and (4) fears about breaches of confidentiality regarding sexual health services or diagnoses noted in medical records or bills. 5 The findings in this report are subject to at least two limitations. First, HEDIS data reflect screenings reported by HMO and POS plans that covered only approximately 30% of U.S. residents in 2001.…”
Section: From the Centers For Disease Control And Preventionmentioning
confidence: 82%
“…However, if a substantial proportion of sexually inactive enrollees had claims for pregnancy tests or oral contraceptives for reasons not related to sexual activity, or if medical claims did not identify all chlamydia tests ordered, HEDIS data would underestimate actual screening rates. Overestimation might occur if a substantial proportion of sexually active enrollees lacked claims for pregnancy, contraceptives, STDs, or Pap tests that would classify them as sexually active in administrative data, 5 or if the measure's numerator included claims for chlamydia tests used to diagnose illness in symptomatic patients. 5 Overestimation also might result if health plans that perform well on the chlamydia screening measure are more likely to report their results to NCQA than those that do not perform as well.…”
Section: From the Centers For Disease Control And Preventionmentioning
confidence: 99%
“…Chlamydia screening was shown to be effective in preventing PID in randomized, controlled trials [4,6,7]. Based on this and other evidence, routine screening for chlamydia has been recommended by individuals and national organizations at different times in the last 15 years [8][9][10][11][12][13] because early detection and treatment has been shown to be costeffective [14][15][16].…”
Section: Introductionmentioning
confidence: 99%